Vitamin D receptor-deficient keratinocytes-derived exosomal miR-4505 promotes the macrophage polarization towards the M1 phenotype - Sun,Wen; Chen,Jianqin; Li,Jingting; She,Xiaoguang; Ma,Hu; Wang,Shali; Liu,Jing; Yuan,Yuan (PeerJ, 2023)
Background The vitamin D receptor (VDR) has a low level of expression in the keratinocytes of patients with psoriasis and plays a role in the development of the disease. Furthermore, the crosstalk between macrophages and psoriatic keratinocytes-derived exosomes is critical for psoriasis progression. However, the effects of VDR-deficient keratinocytes-derived exosomes (Exos-shVDR) on macrophages and their underlying mechanisms remain largely unknown. Methods VDR-deficient keratinocytes were constructed by infecting HaCaT cells with a VDR-targeting lentivirus, mimicking the VDR-deficient state observed in psoriatic keratinocytes. Exosomes were characterized using transmission electron microscopy, nanoparticle tracking analysis, and Western blot. The effect of Exos-shVDR on macrophage proliferation, apoptosis, and M1/M2 polarization was assessed using cell counting kit-8 assay (CCK-8), flow cytometer, real-time quantitative polymerasechain reaction (RT-qPCR), and enzyme-linked immunosorbent assay (ELISA). The mechanism underlying the effect of Exos-shVDR on macrophage function was elucidated through data mining, bioinformatics, RT-qPCR, and rescue experiments. Results Our results revealed that both Exos-shVDR and Exos-shNC exhibited typical exosome characteristics, including a hemispheroid shape with a concave side and particle size ranging from 50 to 100 nm. The levels of expression of VDR were significantly lower in Exos-shVDR than in Exos-shNC. Functional experiments demonstrated that Exos-shVDR significantly promoted macrophage proliferation and polarization towards the M1 phenotype while inhibiting macrophage apoptosis. Moreover, miR-4505 was highly expressed in the skin tissue of patients with psoriasis. Its overexpression significantly increased macrophage proliferation and polarization towards M1 and inhibited apoptosis. Furthermore, the effects of Exos-shVDR on macrophage function occur through miR-4505. Conclusions Exos-shVDR exacerbates macrophage proliferation, promotes polarization towards the M1 phenotype, and inhibits macrophage apoptosis by increasing the levels of miR-4505. These results indicate that modulation of macrophage function is a potential strategy for developing new drugs for the treatment of psoriasis.
Keywords: VDR-deficient keratinocytes; Exosomes; MiR-4505; Macrophage polarization; Psoriasis